Mapping the Embarkation Haji dormitory model equivalent to a star rating hotel to empower local communities and improve the national economy - Sirna, I Ketut; Komalasari, Yeyen; Prasiasa, Dewa Putu Oka (Edelweiss Applied Science and Technology, 2024)
The aim of this research is to map a model for utilizing Hajj dormitories in terms of products, services, management and relevant policies, towards utilizing Hajj dormitories equivalent to star hotels through Hajj dormitory accommodation services to empower local communities and improve the national economy. Specific objective: To realize the management of Hajj dormitories equivalent to star hotels in Indonesia. Research stages: in 2024 research will be carried out on the Medan Hajj embarkation dormitory. Method: This research was carried out descriptively, qualitatively, quantitatively, with a star hotel study approach, as well as community base tourism, as a model for using Hajj dormitories on a par with star hotels. The data was analyzed using the theory of hotel and tourism quality standards, and relevant theories according to the data found at the research site. The research results show a significant value, and equivalently the star hotel rating according to the Ministry of Tourism and Creative Economy no. 53/2013 shows the results, namely: 1). Product with a score of 429, out of 118 elements assessed, 2). Service with a score of 83 out of 31 elements assessed. , 3). Management with a score of 79 out of 20 elements assessed. Fulfillment just needs to improve 9 elements of the standard target score of 600 according to the business requirements for star hotel ratings. The suggestions are: fulfillment of the annual budget needs to be increased to improve product standards, services, training, competency tests, and direct employee involvement, as well as local community empowerment needs to be maximized.